The Gift of a Lifetime: The Hospital, Modern Medicine, and Mortality - Hollingsworth, Alex; Karbownik, Krzysztof; Thomasson, Melissa A.; Wray, Anthony (American Economic Review, 2024)
We explore how access to modern hospitals and medicine affects mortality by leveraging efforts of the Duke Endowment to modernize hospitals in the early twentieth century. The Endowment helped communities build and expand hospitals, obtain state-of-the-art medical technology, attract qualified medical personnel, and refine management practices. We find that Duke support increased the size and quality of the medical sector, fostering growth in not-for-profit hospitals and high-quality physicians. Duke funding reduced both infant mortality—with larger effects for Black infants than White infants—and long-run mortality. Finally, we find that communities aided by Duke benefited more from medical innovations. (JEL I11, I12, J13, J15, L31, N32, O31)